ANALYSIS OF THE EFFECT OF DIGITAL MARKETING AND BRAND IMAGE ON CONSUMER ATTRACTION IN MICRO ENTERPRISES IN THE CULINARY SECTOR OF TENAYAN RAYA - Williya Meta; Aland Polma Naek Sihombing; Wirda Lilia; Delima Jusan Natali (Jurnal Pariwisata Tawangmangu, 2026)
This study aims to analyze the influence of digital marketing and brand image on consumer attraction in micro-enterprises in the culinary sector of Tenayan Raya, Pekanbaru. Employing a quantitative approach with an explanatory research design, data were collected through surveys of 30 micro-businesses that have implemented digital marketing strategies. The results of multiple linear regression analysis indicate that digital marketing has a significant and positive impact on business growth, particularly in enhancing product visibility, market reach, and sales volume. In contrast, brand image does not show a significant effect on consumer attraction, as purchasing decisions are more influenced by functional factors such as taste, price, and word-of-mouth recommendations. These findings highlight the importance of digital adaptation for micro-enterprises as a primary strategy to remain competitive in a dynamic market. Meanwhile, brand image development should be pursued gradually as a long-term strategy once the core business foundations are established. This research provides practical insights for micro-entrepreneurs and policymakers in designing more contextual and locally-relevant MSME development strategies.